Congenital chloride-losing diarrhoea and Crohn's disease: a diagnostic and therapeutic challenge. Issue 2 (19th August 2019) - Harris, Rachel Elizabeth; Tayler, Rachel; Russell, Richard K
Abstract : We describe the case of a patient with congenital chloride-losing diarrhoea (CCLD), global developmental delay and intermittent transaminitis who was diagnosed with Crohn's disease after persistent anaemia and onset of rectal bleeding. CCLD is a rare autosomal recessive condition causing large-volume chloride-rich diarrhoea, metabolic alkalosis and potentially life-threatening electrolyte disturbance. A possible association between CCLD and inflammatory bowel disease (IBD) has recently become apparent; however, the underlying mechanism has not been identified, with the role of increased expression of tumour necrosis factor-alpha hypothesised. Early diagnosis and management are key for favourable outcomes within both CCLD and IBD, and understanding a potential link between the two conditions may lead to development of novel therapies and management strategies. We aim to highlight the pathophysiology, diagnosis and management of CCLD; its potential association with IBD; and the potential therapeutic difficulties within the management of patients with comorbid CCLD and IBD.